How citizen science could improve species distribution models and their independent assessment. Issue 7 (10th March 2021) - Matutini, Florence; Baudry, Jacques; Pain, Guillaume; Sineau, Morgane; Pithon, Joséphine
Abstract: Species distribution models (SDM) have been increasingly developed in recent years, but their validity is questioned. Their assessment can be improved by the use of independent data, but this can be difficult to obtain and prohibitive to collect. Standardized data from citizen science may be used to establish external evaluation datasets and to improve SDM validation and applicability. We used opportunistic presence‐only data along with presence–absence data from a standardized citizen science program to establish and assess habitat suitability maps for 9 species of amphibian in western France. We assessed Generalized Additive and Random Forest Models' performance by (1) cross‐validation using 30% of the opportunistic dataset used to calibrate the model or (2) external validation using different independent datasets derived from citizen science monitoring. We tested the effects of applying different combinations of filters to the citizen data and of complementing it with additional standardized fieldwork. Cross‐validation with an internal evaluation dataset resulted in higher AUC (Area Under the receiver operating Curve) than external evaluation causing overestimation of model accuracy and did not select the same models; models integrating sampling effort performed better with external validation. AUC, specificity, and sensitivity of models calculated with different filtered external datasets differed for some species. However, for most species, complementary fieldwork was not necessary to obtain coherent results, as long as the citizen science data were strongly filtered. Since external validation methods using independent data are considered more robust, filtering data from citizen sciences may make a valuable contribution to the assessment of SDM. Limited complementary fieldwork with volunteer's participation to complete ecological gradients may also possibly enhance citizen involvement and lead to better use of SDM in decision processes for nature conservation. Abstract : To develop new scientific and participatory approaches might better integrate biodiversity issues into decision‐making processes. In this study, we used different datasets to establish and assess habitat suitability maps for 9 species of amphibian in France. We compared different SDM as well as the effect of integrating parameters relating to sampling effort. We assessed the models' performance by (1) internal cross‐validation or (2) external validation using an independent dataset from citizen science monitoring strategically completed. The AUC values obtained with cross‐validation were much higher for all species than with external evaluation and models integrating sampling effort performed better with external validation methods. Data from citizen science may help to get valuable external dataset to the assessment of SDM.